A MicroRNA Derived From Schistosoma japonicum Promotes Schistosomiasis Hepatic Fibrosis by Targeting Host Secreted Frizzled-Related Protein 1 - Wang, Yange; Fan, Xiaobin; Lei, Nanhang; He, Xing; Wang, Xiaoxi; Luo, Xufeng; Zhang, Dongmei; Pan, Weiqing (Frontiers in Cellular and Infection Microbiology, 2020)
Schistosomiasis remains a serious parasitic disease, which is characterized by granulomatous inflammation and hepatic fibrosis. MicroRNAs derived from parasites can regulate host genes and cell phenotype. Here, we showed that a miRNA of Schistosoma japonicum (Sja-miR-1) is consistently present in the hepatic stellate cells (HSCs) of infected mice and up-regulates the expression of collagens and α-SMA by targeting secreted frizzled-related protein 1. A vector-mediated delivery of Sja-miR-1 into naive mice led to hepatic fibrogenesis in the mice. Accordingly, inhibition of Sja-miR-1 in the infected mice led to reduction of the parasite-induced hepatic fibrosis. The mechanism behind the Sja-miR-1-mediated activation of HSC is through targeting secreted frizzled-related protein 1 to regulate the Wnt/β-catenin signaling pathway. These findings reveal that parasite-derived small non-coding RNAs are implicated in cross-species regulation of host pathological process and persistent inhibition of these parasite-derived miRNAs may provide a potential therapeutic intervention for infectious diseases.